LITURGI SEBAGAI MODEL BERPASTORAL - Epafras Mario Lumunder; Tifany Fergie Tombokan; Samuel Wailan Leonard Wanget (POIMEN Jurnal Pastoral Konseling, 2023)
Liturgy, often thought of as simply the manner of worship, actually has a broader meaning. From the Greek, liturgy comes from "leiturgia," which includes the meaning of serving and working for the community. Initially, liturgy had political and profane connotations, only to develop into a cultic aspect in the second century AD. In the cultic context, liturgy is defined as a worship service that involves the active participation of the people. Rasid Rachman emphasized that liturgy also includes daily worship practices and reflects the belief and communion of the people with God. The importance of liturgy in the church lies in its role in animating belief and shining the love of Christ. Liturgy is at the core of the church, enabling interaction between the people and God, as well as the renewal of God's covenant with His people. Every element of the liturgy, from ordination to blessing, carries deep pastoral meaning. However, challenges arise when different generations feel incompatible with existing forms of worship. Therefore, contextualization of liturgy is important, following the changing times and understanding the needs of the congregation. In developing a living liturgy, it is important to note that liturgy is not a performance, but rather a worship that involves all the people. The pastoral aspect of liturgy emerges when people unite in worship, creating a unique space where God's grace can operate. Contextualization of liturgy, as outlined by Rasid Rachman, involves adjusting to the necessary context, including in the increasingly advanced times. This study uses the library research method to understand the meaning of liturgy as a pastoral effort. Data were obtained through literature study and grouped by theme and then processed using content analysis method. The results of the discussion include the meaning of liturgy, pastoral functions, and the importance of contextualizing liturgy in conveying religious messages with relevance in everyday life.